2015
DOI: 10.1007/s13738-015-0700-2
|View full text |Cite
|
Sign up to set email alerts
|

Aminopyridinium iodide as a NH transferring agent for the synthesis of 2-aroyl-3-aryl aziridines

Abstract: by bromination of the related α,β-unsaturated carbonyl compounds, followed with the reaction of ammonia solution [5][6][7][8][9][10].Another synthetic pathway for the synthesis of aziridinyl ketones involves formation of β-hydroxyamino derivatives followed by treatment with either metal alcoholates, or hydroxylamine hydrochloride and then potassium hydroxide [11][12][13][14]. It has been reported the interaction of unsaturated ketones with N-tosyliminoaryliodinanes in the presence of mono-valent copper complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In 2015, Samimi reported that another amination reagent 1-aminopyridinium iodide can also carry out the aziridination of chalcone. 11 The proposed mechanism is as follows: the tertiary amine reacted in situ to produce the hydrazinium salt 7 and regenerated as a leaving group; it is believed that the tertiary amine could theoretically act as a catalyst (Scheme 5). In 2006, the Shi group first reported a catalytic process for the synthesis of α-keto aziridines from chalcones.…”
Section: Aziridination Of Olefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Samimi reported that another amination reagent 1-aminopyridinium iodide can also carry out the aziridination of chalcone. 11 The proposed mechanism is as follows: the tertiary amine reacted in situ to produce the hydrazinium salt 7 and regenerated as a leaving group; it is believed that the tertiary amine could theoretically act as a catalyst (Scheme 5). In 2006, the Shi group first reported a catalytic process for the synthesis of α-keto aziridines from chalcones.…”
Section: Aziridination Of Olefinsmentioning
confidence: 99%
“…In 2015, Samimi reported that another amination reagent 1-aminopyridinium iodide can also carry out the aziridination of chalcone. 11…”
Section: Reaction Of Hydrazinium Saltsmentioning
confidence: 99%